APLICAÇÃO DE VITAMINAS COMO TECNOLOGIA DE AMENIZAÇÃO DE ESTRESSE EM MILHO - SILVA FILHO, Marcelo Xavier,; COSTA, Antonio Cesar,; VENDRUSCOLO, Eduardo Pradi,; ARAÚJO, Thales Oliveira,; SERON, Cássio de Castro,; MARTINS, Murilo Battistuzzi, (ANAIS DO ENIC, 2023)
-